Psychedelic iatrogenic structural dissociation: an exploratory hypothesis on dissociative risks in psychedelic use - Elfrink, Steven; Bergin, Leigh (Frontiers in Psychology, 2025)
This paper introduces the hypothesis of Psychedelic Iatrogenic Structural Dissociation (PISD), proposing that psychedelics may reactivate dissociated traumatic material, increasing the risk of psychological destabilization in trauma-exposed individuals. Grounded in structural dissociation theory, this framework suggests that psychedelics can disrupt the balance between daily functioning (the Apparently Normal Personality, ANP) and trauma-related responses (the Emotional Personality, EP), leading to the resurfacing of unintegrated memories. A review of recent studies highlights persistent adverse effects associated with psychedelic use, including emotional dysregulation, identity fragmentation, derealization, and perceptual disturbances, particularly among individuals with early trauma histories. To mitigate these risks and facilitate trauma processing, integration practices, body-focused therapies, and structured social support systems are proposed as key interventions. Additionally, emerging neurophysiological models suggest that psychedelics may reconfigure dissociative processes through the modulation of entrenched patterns, potentially facilitating trauma integration or increasing vulnerability to destabilization, depending on individual and contextual factors. These findings underscore the necessity of trauma-informed screening, preparation, and integration protocols to enhance the safety and efficacy of psychedelic therapies, particularly for vulnerable populations.